Apatinib treatment combined with chemotherapy for advanced epithelial ovarian cancer: a case report - Deng, Linghui (Onco Targets Ther, 2017)
Apatinib is a novel oral tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor-2, which has been proved by clinical trials to be effective and safe for patients with chemotherapy-refractory gastric cancer. To date, there is no study or case report on apatinib treatment for patients with ovarian cancer. Here, we present the case of a 50-year-old Chinese woman with advanced ovarian cancer, who received apatinib at a daily dose of 500 mg for 28 days per cycle after failure of fourth-line chemotherapy. Favorable oncologic outcome was achieved in this case after treatment with apatinib. The patient’s progression-free survival is now 11.3 months, and she is taking apatinib and capecitabine as maintenance treatment. The common side effect of apatinib was fatigue; however, the toxicity of apatinib was controllable and tolerable. Thus, apatinib may be an option for chemotherapy-refractory advanced epithelial ovarian cancer, but this still warrants further investigation.